Aerodynamic characteristics of generic ice shells. Issue 184 (January 2019) - Raeesi, Arash; McTavish, Sean; D'Auteuil, Annick
Abstract: Freezing rain and wet snow can cause ice to accumulate on the surface of bridge cables. Subsequently, a rise in temperature and wind can cause ice to shed from the surface of cables. Several instances of ice and wet snow shedding from bridge cables have been observed in Canada. Environmental predictive models have been proposed to predict the ice shedding behaviour and its trajectory from bridge cables. The current study aims at measuring the aerodynamic force and moment coefficients of generic ice fragments detached from a bridge cable as a priori for a subsequent ice trajectory model. Nine representative generic, ice shells were selected to represent different aspect ratios, curvatures, ice thicknesses, and external ice surface conditions. Aerodynamic forces and moments were measured for each of the ice shell models in turbulent flow for a wide range of orientations. The use of a curved shape as opposed to a flat plate resulted in a significant difference in the aerodynamic coefficients. It was found that the aspect ratio was the most important geometric factor in determining the aerodynamic forces and moments on the curved models. The findings of this study will be implemented in future ice trajectory models. Highlights: Ice fragments could shed from bridge cables posing safety risks to traffic and pedestrians. Aerodynamic characteristics of generic ice shells were studied for a wide range of orientations. Aspect ratio was the most important factor in determining the aerodynamic force and moments. The results of this study will be implemented in ice trajectory models.